A local spatio-temporal approach to plane wave ultrasound particle image velocimetry - Bodnariuc, Ecaterina; Petra, Stefania; Schnörr, Christoph (Pattern Recognition, 2017)
We present a simple and efficient approach to plane wave ultrasound particle image velocimetry (Echo PIV). Specifically, a carefully designed bank of local motion-sensitive filters is introduced, together with a method for non-linear flow parameter estimation based on time-averaged local flow estimates. The approach is validated and quantitatively assessed using both simulated and in-vitro real data, in scenarios with laminar as well as with turbulent flow.
Gesehen am 12.03.2018